Load transfer in phase transforming matrix–nanowire composite revealing the significant load carrying capacity of the nanowires. (5th January 2016) - Yu, Cun; Liu, Zhenyang; Liu, Yinong; Shao, Yang; Ren, Yang; Cui, Lishan
Abstract: This paper reports a study of an in-situ composite of NiTi matrix and aligned Nb nanowires. The design strategy of the composite was to further explore the load carrying capacity of the nanowire reinforcements in composite. This composite system offered a unique condition of load sharing between the two components in which the NiTi matrix deforms via discrete (discontinuous), instantaneous and intrinsic lattice distortion through stress-induced martensitic transformation (SIMT) and the Nb nanowires deform via elastic deformation. This study investigated the mechanism of load sharing between the embedded Nb nanowires and the NiTi matrix by means of in-situ synchrotron diffraction analysis. It was found that significant load transfer from the matrix to the nanowires occurred when the NiTi matrix underwent stress-induced B2–B19′ martensitic transformation and the nanowires deformed largely by elastic deformation. The embedded Nb nanowires, with a volume fraction of 25%, were revealed capable of carrying at maximally 70% of the applied load at the completion of SIMT of NiTi matrix, and were capable of carrying more than 55% of the applied load at the terminal of deformation. Graphical abstract: Highlights: The manuscript reports a study on a novel metallic composite, the elastic strain limit of nanowires in which was knocked down. The embedded Nb nanowires with 25% volume fraction were revealed capable of carrying at maximally 70% of the applied load. The underlying mechanism of such material design was studied by means of high energy X-ray diffraction. The key to exploring mechanical capacity of nanowire is the load transfer from NiTi matrix to nanowires during SIMT.